PENGARUH GAYA MENGAJAR GURU TERHADAP MOTIVASI BELAJAR SISWA PADA KOMPETENSI DASAR SISTEM REM DI SMK CIPTA KARYA PREMBUN - Angga Setiawan; Aci Primartadi; Suyitno (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine: (1) the effect of teachers’ teaching style on students’ learning motivation in the brake system basic competency learning at Class XI Light Vehicle Engineering SMK Cipta Karya Prembun Kebumen; and (2) a description of the teaching styles (authoritative, democratic, and permissive) applied by teachers in that context. A quantitative ex post facto correlational design was used. The population consisted of all 50 Class XI TKR students (academic year 2025/2026), taken using proportional random sampling via Slovin’s formula (e = 5%). Data were collected through a 24-item Likert-scale questionnaire for each variable, validated with Pearson Product Moment correlation (r-table = 0.28, all items valid) and reliability-tested with Cronbach’s Alpha (X = 0.873; Y = 0.930). Prerequisite tests confirmed normality (K-S sig. = 0.151 > 0.05), linearity (Deviation from Linearity sig. = 0.655 > 0.05), and homogeneity (Levene’s sig. > 0.05). Pearson correlation showed a strong and significant relationship (r = 0.611; sig. = 0.000). Simple linear regression produced the equation Y = 24.511 + 0.766X (t = 5.353; sig. = 0.000), indicating that every one-unit increase in teaching style raises learning motivation by 0.766 units. The coefficient of determination R² = 0.374 shows that teaching style accounts for 37.4% of variation in learning motivation, while 62.6% is attributable to other factors. Descriptively, the authoritative teaching style had the highest mean score (33.72) compared to democratic (32.76) and permissive (31.36), confirming its dominance in brake system practical learning.